Simile the novel Yusuf and Zulaikha by Hakim Nuruddin Abdurrahman Jami translated into englishhby David pendlebury - Maemunah (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2022)
wt,1/irh,c.1